Thoughts on the ideological perspective in the comprehension of the city and built heritage in Latin America (Ciudades, 2018)
Long and never easy, especially  for Latin Americans, has been the discussion on the topic that frames and subscribes to the historical and conceptual consideration of cities and built heritage, of the cultural continent formed by more than twenty countries.
Keywords: ideological perspective; city; built heritage; Latin America